2010
DOI: 10.1073/pnas.0911813107
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Plasmodium falciparum M17 aminopeptidase and significance for the design of drugs targeting the neutral exopeptidases

Abstract: Current therapeutics and prophylactics for malaria are under severe challenge as a result of the rapid emergence of drug-resistant parasites. The human malaria parasite Plasmodium falciparum expresses two neutral aminopeptidases, Pf A-M1 and PfA-M17, which function in regulating the intracellular pool of amino acids required for growth and development inside the red blood cell. These enzymes are essential for parasite viability and are validated therapeutic targets. We previously reported the x-ray crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
168
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(173 citation statements)
references
References 38 publications
5
168
0
Order By: Relevance
“…The active site of PfA-M1 is enclosed deep within the catalytic domain and is accessed by putative substrate entry and exit channels [9]. In contrast, the six active sites of PfA-M17 are located on the edge of the catalytic domain, and exposed to solvent in the interior cavity of the hexameric assembly [12]. Despite these major differences between PfA-M1 and PfA-M17, the enzymes share similar architecture within the active sites ( Fig.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…The active site of PfA-M1 is enclosed deep within the catalytic domain and is accessed by putative substrate entry and exit channels [9]. In contrast, the six active sites of PfA-M17 are located on the edge of the catalytic domain, and exposed to solvent in the interior cavity of the hexameric assembly [12]. Despite these major differences between PfA-M1 and PfA-M17, the enzymes share similar architecture within the active sites ( Fig.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…1A and 1B). These similarities prompted suggestions that a single compound capable of inhibiting both enzymes could be developed [12]. A drug that can effectively inhibit more than one target could potentially slow the emergence of drug resistance parasites.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1) [33], with the most lipophilic, 8c, being also the most active anti-plasmodial; amino acid and dipeptide esters are known to cross cell membranes by passive diffusion [38], so it is possible that the presence of the dipeptide spacer in HEDICINs augments cell permeation of these compounds by such process; b) recognition of the dipeptide motif by specific transporters from the P. falciparum ABC transporter super-family, many of which have been taken as putative drug transporting proteins [39] and found to be directly implicated in drugresistance mechanisms [40,41]; c) increased permeability of dipeptide derivatives due to the new permeation pathways created in P. falciparum-infected RBCs to promote uptake of nutrients such as sugars or nucleosides [42], as well as amino acids and oligopeptides [31]; II. Alternatively, a difference in the respective mechanism of action (MOA) may be operating in addition, or in alternative, to a difference in uptake of HEDICINs versus HECINs: a) due to their dipeptide moiety, HEDICINs might be able to inhibit plasmodial cytosolic proteases like aminopeptidases PfA-M1 and PfA-M17, which function in regulating the intracellular pool of amino acids required for parasite growth and development inside the red blood cell [43,44]; b) HEDICINs anti-plasmodial activity could otherwise be related to the cinnamoyl moiety, as it has been shown that cinnamic acid derivatives inhibit the growth of intraerythrocytic P. falciparum in culture by inhibiting monocarboxylate (e.g. lactate) transport and translocation of other nutrients, as carbohydrates and amino acids required for parasite nourishment [45]; c) finally, HEDICINs anti-plasmodial activity could as well be due to inhibition of the new permeation pathways; meaning that HEDICINs could eventually block the new permeation pathways created in infected RBC (see above, I.c), hampering the uptake of molecules essential to the parasite; it is interesting to notice that amongst our most active molecules as antiplasmodials are those bearing a nitro-aryl moiety, also present in potent new permeation pathways inhibitors such as 5-nitro-2-(phenylalkylamino) benzoic acid derivatives [31].…”
Section: Fukui Indices Of the Vinyl Carbons In Hecinsmentioning
confidence: 99%